Non-Host Status of Green Lemon Fruit (Citrus × limon (L.) Burman f. cv. Lisbon) to Oriental Fruit Fly, Mediterranean Fruit Fly, and Melon Fly (Diptera: Tephritidae) in Hawaii - Peter A. Follett; Xiuxiu Sun; Spencer S. Walse (Insects)
We investigated the host status of harvest-ready green lemons, Citrus × limon (L.) Burm. F. cv. Lisbon (Rutaceae), to Oriental fruit fly (Bactrocera dorsalis), Mediterranean fruit fly (Ceratitis capitata), and melon fly (Zeugodacus cucurbitae) (Diptera: Tephritidae) in Hawaii using laboratory and field studies. In forced-infestation small-cage exposures (using 25 × 25 × 25 cm screened cages with 50 gravid females), punctured lemons were infested by Oriental fruit fly, Mediterranean fruit fly, and melon fly, whereas undamaged lemons were not infested. Field collection, packing, and incubation of approximately 58,420 mixed-grade fruit (commercial export quality and off grades) found no natural infestations and resulted in no fruit fly emergence. Field studies enclosing fruit on trees in sleeve cages that were stocked with 50 gravid females per cage resulted in no infestations. Commercial export-grade green Lisbon lemon fruit should, therefore, be considered a non-host for Oriental fruit fly, Mediterranean fruit fly, and melon fly.